The Influence of Inquiry-Based Learning on Students’ Understanding of Accounting Concepts - Aurelio Rizqi Pratama (Institute of Accounting Research and Novation (IARN), 2024)
This study examines the impact of the Inquiry-Based Learning (IBL) model on students' understanding of accounting concepts in comparison to traditional lecture-based teaching methods. The research aimed to determine whether IBL could foster deeper comprehension, enhance critical thinking, and improve the application of accounting principles in real-world scenarios. The study involved two groups of accounting students: one taught using IBL strategies and the other using conventional teaching methods. Pre- and post-test assessments were conducted to measure academic performance, while interviews provided qualitative insights into student engagement and learning experiences. The results revealed that students in the IBL group showed significantly higher post-test scores, with a marked improvement in their ability to analyze and apply accounting concepts. Furthermore, qualitative data indicated that IBL encouraged greater student participation, critical thinking, and motivation to learn. These findings suggest that IBL is a more effective pedagogical approach for enhancing students' understanding of accounting concepts, fostering active engagement, and promoting lifelong learning skills. This research contributes to the growing body of evidence supporting the integration of active learning strategies in accounting education and recommends the adoption of IBL in curricula to improve student outcomes and better prepare them for the demands of the professional world.